Out-of-pocket Expenditure and its Impact on the Quality of Life among Patients Attending the Anti-retroviral Therapy Centre of a Tertiary Care Hospital in Kolkata - Mamunur Rashid; Dipendra Narayan Goswami; Kuntala Ray; Mausumi Basu; Aparajita Mondal; Abhipsa Dey (Indian Association of Preventive and Social Medicine, 2024)
Introduction: Out-of-pocket expenditure (OOPE) has a negative impact on Quality of life (QoL) of People Living with HIV (PLHIV)which can increase the risk of slipping into poverty. Objectives: Primary Objective of this study was to estimate the burden of OOPE in seeking health care among HIV patients attending the Anti-retroviral therapy (ART) centre of a tertiary care hospital; and secondary objectives were to assess their QoL, to identify the association of socio-demographic characteristics with the OOPE & QoL and to find out the correlation between OOPE and QoL. Method: A cross-sectional study was conducted among 232 patients attending ART centre of a tertiary care hospital in Kolkata using a pre-designed, pre-tested, structured schedule. Multivariable binary logistic regression was done to identify the association of their socio-demographic characteristics and clinical profile with the OOPE and QoL. Results: About 41.4% of the study population rated their QoL as neither poor nor good, 18.9% as 'good'. All the participants reported OOPE; 20.7% in the form of direct health expenditure. Participants belonging to the age group 18-39 years, residing in a joint family, had family member infected with HIV and had associated co-morbidity were statistically significant covariates of direct health expenditure; whereas participants belonging to the age group ≥40 years, living in a joint family, involved in an unskilled occupation, and belonging to middle and lower middle were statistically significant covariates of poor QoL. Conclusion: OOPE was experienced by all participants. As per the study findings Qol was neither poor nor good among participants. With increase in OOPE, the QoL worsened.